Dinuclear clathrochelate complexes with pendent cyano groups as metalloligands. Issue 39 (12th September 2016) - Marmier, Mathieu; Cecot, Giacomo; Vologzhanina, Anna V.; Bila, José L.; Zivkovic, Ivica; Ronnow, Henrik M.; Nafradi, Balint; Solari, Euro; Pattison, Philip; Scopelliti, Rosario; Severin, Kay
Abstract : Dinuclear clathrochelate complexes can be decorated with two, three, four, or five cyano groups. These complexes represent versatile metalloligands for the construction of coordination polymers. Abstract : Dinuclear clathrochelate complexes with two, three, four, or five cyano groups in the ligand periphery were prepared following two distinct synthetic strategies: (a) zinc(ii )- or cobalt(ii )-templated polycondensation reactions of CN-functionalized arylboronic acids and phenoldioximes, or (b) postsynthetic cross-coupling reactions of polybrominated zinc(ii ) clathrochelates with 4-cyanophenylboronic acid. The new clathrochelate complexes were used as metalloligands for the construction of heterometallic Zn 2+ /Ag + and Co 2+ /Ag + coordination polymers (CPs), which were characterized by single crystal X-ray diffraction and FT-IR. A one-dimensional CP was observed for ditopic clathrochelates, whereas two- and three-dimensional CPs were generated from tetra- and pentatopic metalloligands. The three-dimensional network is unique as it displays an unprecedented network topology with the point symbol (8·10 2 )(8 2 ·10 4 )(8 2 ·10)(8 3 ·10 3 ). Furthermore, it is a self-catenated net with an extremely high topological density.